2021
DOI: 10.1093/cid/ciaa1530
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anti–PD-1 and Anti–CTLA-4 on the Human Immunodeficiency Virus (HIV) Reservoir in People Living With HIV With Cancer on Antiretroviral Therapy: The AIDS Malignancy Consortium 095 Study

Abstract: Background Antibodies to PD-1 and CTLA-4 may perturb HIV persistence during antiretroviral therapy (ART) by reversing HIV-latency and/or boosting HIV-specific immunity leading to clearance of infected cells. We tested this hypothesis in a clinical trial of anti-PD-1 alone or in combination with anti-CTLA-4 in people living with HIV (PLWH) and cancer. Methods This was a substudy of the AIDS Malignancy Consortium-095 Study. ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 38 publications
4
46
1
Order By: Relevance
“…Other small case series or case reports in PWH on ART with concomitant malignancy have similarly shown an increase in HIV-specific CD4 1 and CD8 1 T cells in some but not all participants following antiPD-1 treatment (16,17). There are currently seven clinical trials of antiPD-1 enrolling PWH on ART, including three studies enrolling people without cancer (https://clinicaltrials.gov) and one study evaluating the impact of antiPD-1 and antiCTLA-4 (18).…”
mentioning
confidence: 99%
“…Other small case series or case reports in PWH on ART with concomitant malignancy have similarly shown an increase in HIV-specific CD4 1 and CD8 1 T cells in some but not all participants following antiPD-1 treatment (16,17). There are currently seven clinical trials of antiPD-1 enrolling PWH on ART, including three studies enrolling people without cancer (https://clinicaltrials.gov) and one study evaluating the impact of antiPD-1 and antiCTLA-4 (18).…”
mentioning
confidence: 99%
“…Additionally, in a new clinical trial (ClinicalTrials.gov Identifier: NCT02408861), participants with HIV associated classical Hodgkin lymphoma or solid tumors received ipilimumab and nivolumab (anti-PD-1). An increase in CA-US HIV RNA following infusion was noted, whereas anti-PD-1 alone had no effect on HIV-latency or the latent HIV-reservoir (141).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 88%
“…It may be that viral antigens interfere with the anti-tumor effects of anti-PD-1 in the tumor immune microenvironment (TME). However, a sub-study of the Acquired Immunodeficiency Syndrome Malignancy Consortium-095 Study recently reported that anti-PD-1 alone had no effect on HIV-latency or the latent HIV-reservoir (20). More importantly, Sun et al (13) found no significant association between HBV loads and survival in HCC patients.…”
Section: Discussionmentioning
confidence: 99%